Gestión ambiental local en el sector industrial de DMQ - Escalante Viteri, Gloria Cecibel (2015)
This research is about the local environmental management in the industrial sector of the Metropolitan District of Quito. The Metropolitan District of Quito is considered an administrative, economic development of the country and facing various problems of urban air pollution, including industrial activities caused by heart. It is important to analyze pollution from manufacturing activities as Quito is one of the main centers of industrial development in the country and inadequate environmental management in the productive sector would cause a greater contribution to environmental degradation of the city if corrections are not established. The present study aims to determine whether environmental management by the capital's industry contributes to building a sustainable city or simply responds to the obligation to comply with local environmental regulations. For this analysis of environmental management model implemented by the Metropolitan Environmental Directorate of DMQ, currently Secretary of Environment in relation to industrial .It takes as study period the years 2008, 2009, 2010, 2011 and 2012 is performed where was in effect Metropolitan Ordinance No. 213 "On the Prevention and Control of the Environment". The description of the environmental management model adopted for industrial activities leads to the generation of management indicators and environmental quality, which are intended to complement the analysis using real data. The indicators are related to compliance with maximum permissible limits for liquid discharges, air emissions from stationary combustion and noise emissions. Also, consider breaches of environmental management plans, citizen complaint registered with the Environmental Police, the funds raised by the Environmental Fund for fines and penalties, among others. This information was obtained from the processing of the databases of the Ministry of Environment. The identification of institutional actors, their roles and interactions within the field of environmental management developed by the industry is one of the aspects considered, which aims to collect the different perceptions and points of view regarding this issue. From the information collected is intended that the results and conclusions obtained 15 objectively contribute to improving the management of environmental problems caused by capital industry so that the resulting environmental impacts are controlled ensuring the preservation and improvement of environmental quality of the city; and that in the near future the industrial sector is one of the main actors to promote and contribute to a sustainable city is Quito. With this research the current situation of environmental management is described and possible axes are determined to establish public policies for local environmental management in the industrial sector of the DMQ.